STRENGTHENING RELIGIOUS MODERATION THROUGH DEEP-LEARNING-ASSISTED LOCAL-WISDOM LEARNING MATERIALS IN ISLAMIC BOARDING SCHOOLS - Ahmad Zainuri; Mukti Ali; Muhtarom Muhtarom (Institut Agama Islam Al Hidayah Bogor, 2026)
The rapid development of artificial intelligence (AI) offers new opportunities for educational, however, its role in value-oriented Islamic education remains insufficiently understood, particularly in relation to culturally grounded learning and religious moderation. This study examines how deep-learning-assisted local-wisdom learning materials contribute to strengthening religious moderation in Islamic boarding schools (pesantren) while preserving cultural authenticity and teacher mediation. A sequential exploratory mixed-methods design was employed across seven pesantren in South Sumatra, Indonesia. Qualitative data were collected through interviews, observations, and document analysis involving 30 teachers and 12 pesantren leaders and were thematically analyzed using NVivo 12 Plus. The quantitative phase involved a questionnaire administered to 250 students to examine moderation-related responses. The findings reveal a complementary relationship among technology, culture, pedagogy, and social experience. Deep-learning-assisted technology primarily supported the organization, contextualization, and enrichment of learning materials and facilitated conceptual understanding, while local wisdom provided cultural authenticity and contextual relevance. Teachers played a critical role in ensuring the cultural, religious, and pedagogical appropriateness of technology-assisted materials. Most importantly, direct social experiences, including group discussions, cooperation, communal religious practices, and everyday interactions, emerged as the primary context for internalizing moderation values. Quantitative responses showed positive patterns in tolerance understanding, discipline, and cooperation. The study concludes that religious moderation is strengthened not through technological intervention alone but through the integration of technological support, culturally grounded knowledge, teacher mediation, and lived social experience. These findings offer a human-centered and culturally responsive framework for integrating AI-assisted learning into pesantren education.